Six complete mitochondrial genomes of mayflies from three genera of Ephemerellidae (Insecta: Ephemeroptera) with inversion and translocation of trnI rearrangement and their phylogenetic relationships - Xiao-Dong Xu (PeerJ, 2020)
As a small order of Pterygota (Insecta), Ephemeroptera has almost 3,500 species around the world. Ephemerellidae is a widely distributed common group of Ephemeroptera. However, the relationship among Ephemerellidae, Vietnamellidae and Teloganellidae is still in dispute. In this study, we sequenced six complete mitogenomes of three genera from Ephemerellidae (Insecta: Ephemeroptera): Ephemerella sp. Yunnan-2018, Serratella zapekinae, Serratella sp. Yunnan-2018, Serratella sp. Liaoning-2019, Torleya grandipennis and T. tumiforceps. These mitogenomes were employed to reveal controversial phylogenetic relationships among the Ephemeroptera, with emphasis on the phylogenetic relationships among Ephemerellidae. The lengths of the six mayfly mitogenomes ranged from 15,134 bp to 15,703 bp. Four mitogenomes of Ephemerella sp. Yunnan-2018, Serratella zapekinae, Serratella sp. Yunnan-2018 and Serratella sp. Liaoning-2019 had 22 tRNAs including an inversion and translocation of trnI. By contrast, the mitogenomes of T. tumiforceps and T. grandipennis had 24 tRNAs due to an extra two copies of inversion and translocation of trnI. Within the family Ephemerellidae, disparate gene rearrangement occurred in the mitogenomes of different genera: one copy of inversion and translocation trnI in the genera Ephemerella and Serratella, and three repeat copies of inversion and translocation of trnI in the genus Torleya. A large non-coding region (≥200 bp) between trnS1 (AGN) and trnE was detected in T. grandipennis and T. tumiforceps. Among the phylogenetic relationship of the Ephemeroptera, the monophyly of almost all families except Siphlonuridae was supported by BI and ML analyses. The phylogenetic results indicated that Ephemerellidae was the sister clade to Vietnamellidae whereas Teloganellidae was not a sister clade of Ephemerellidae and Vietnamellidae.